Subsídios para a gestão dos planos de aplicação de vinhaça (PAV): um estudo de caso da região de Piracicaba - Diniz, Kátia Maria (2010)
Concomitant with the production of ethanol from the fermentation of different raw materials (sugar cane, sugar beet, corn, wheat, potatoes, cassava) the vinasse is produced. The vinasse from sugar cane is generated in the average proportion of 12 liters for every liter of ethanol. Brazil is the world's largest producer of sugarcane (570 million tons in 2009). It has produced 27 billion liters of ethanol per year, in the 2009/2010 cycle, primarily for fuel purposes, and therefore the amount of vinasse produced is around 320 billion liters per year. Among the possible usages of vinasse, such as concentration, chemical and biological treatment or production of biomass, the most common form of its disposition is soil application. However, its application in soil can not be excessive or indiscriminate, failing to endanger the environment and profitability of agricultural and industrial sugarcane plantation. The need for control measures on the application of vinasse on the soil in the State of Sao Paulo, which concentrates 60% of the production of ethanol produced in Brazil, led to the drafting of the Technical Regulation P4.231 in 2005. The establishment of the effective items of this regulation is one of the inspector agent’s actions, in the monitoring of the conception and destination of the vinasse by the ethanol-producing undertakers. Items 5.7.1 and 5.7.2 in this regulation make mandatory the referral to CETESB (Environmental Company of São Paulo), for purposes of monitoring and surveillance, until April 02 of each year, the Vinasse Application Plan (VAP). In order to provide better understanding of the Regulation P4.231 and contribute to the optimization of its applicability and to improve and understanding the practical reality of vinasse application there were analyzed VAPs filed in the Environmental Agency of Piracicaba by carrying out licenses issued, licensing procedures and inspections. It is possible to conclude that the Regulation P4.231 represents a breakthrough in managing the use of vinasse in São Paulo, by the disciplinary provision of vinasse on the soil, making it mandatory: demarcation of protected areas and population centers, soil and vinasse characterization and vinasse full doses to be applied, studies of geology and hydrogeology sites, monitoring of groundwater, waterproofing of tanks and pipelines. It establishes criteria to be obeyed by law, and all pipes are good practices to protect environment, which result in greater agricultural and industrial profitability. The Regulation P4.231 is well designed, complex and extensive, making it difficult to implement. To facilitate its applicability, it is suggested to establish a schedule of priorities: waterproofing of tanks and pipes, drains control with optimized operation and good characterization of what is being applied, pure or mixed vinasse with wastewater. Among the eight companies in this study, only 4 (the biggest ones) are filing the VAPs regularly since 2005. The information presented was incomplete and in some cases, insufficient. Even with gaps, all data provided from the beginning of the mandatory VAP was helpful to outline the profile of ethanol activity in this studied region.